Optimalisasi Strategi Pemasaran Properti Menggunakan Platform Nuelink pada PT. Dewe Makmur Mapan - Afifani Aulida Romadhoni; Andry Rachmadany (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Businesses in the increasingly competitive property industry must structuredly and efficiently optimize their digital marketing strategies. PT. Dewe Makmur Mapan faces several key issues. These include inconsistent content publication, limited promotional video production, and underutilization of the Nuelink social media management platform to support effective marketing. The purpose of this community service is to optimize the scheduling, production, and evaluation of digital content using a participant observation approach. This approach includes problem identification, strategy implementation, and content performance analysis. Improved promotional video production and editing with CapCut, AI-based copywriting, structured scheduling and publication with Nuelink, and the utilization of analytical features for data-driven evaluation, among other solutions, were explored. The results of the activity showed increased upload consistency, content variety, audience engagement (likes, views, and comments), and more consistent follower growth. The division of roles between paid advertising and organic content management improved the effectiveness of marketing operations. Based on the results of the activity, it was concluded that optimizing social media management platforms simultaneously can increase audience engagement, promotional reach, and the effectiveness of digital marketing for property businesses.